PRINCIPLES OF RENEWAL OF POETIC FORM - Tajibayeva Latofat Farhodovna (International Journal of Innovations in Engineering Research and Technology, 2023)
This article talks about stylistic updates and stylistic changes in new Uzbek poetry. It has been scientifically proven that the substantive change that began with the works of Furqat, Kamil Khorezmi, and Zavqi has undergone a formal change in the works of Fitrat and Cholpan.